Atheism in its contemporary form and methods of dealing with it in light of the Islamic faith (Journal of the College of Basic Education, 2025)
Contemporary atheism is an ancient and complex phenomenon with deep roots in Islamic society. It has become difficult to find a society these days that is free of any manifestation of atheism, or that is not touched by even the slightest bit of its atheistic pollutants mixed with civil life. This is because most Islamic societies do not have a correct conception of the true Islamic religion, represented by the Book of God and the Sunnah of His Messenger (peace and blessings be upon him), due to their distance from the true fundamentals of the religion. Contemporary new atheism has become a major threat to Islamic societies, in one way or another. Atheism is the denial of the existence of the Creator God, the origin of all origins and the foundation of all premises